Seven Cases of Ossification of the Posterior Longitudinal Ligament which occurred in Patients with Rheumatoid Arthritis - SAKURAI Takeo; 磯 武信; 大宜見 綱夫; 宇田川 英一; 佐野 潔; 井上 博; 竹内 公彦; 根岸 龍一; 岸 和司 (Japanese Journal of Rheumatism and Joint Surgery, 1991)
We have experienced 7 RA patients with ossification of the posterior longitudinal ligament of the spine (OPLL) . According to lateral X-ray pictures, 5 cases were segmental type and 2 cases were mixed type. The results showed that segmental ossification is more frequent in OPLL with RA than in ordinary OPLL. No spinal cord dysfunction suspected of being associated with OPLL was noted.